2003
DOI: 10.1053/jlts.2003.50027
|View full text |Cite
|
Sign up to set email alerts
|

A correlation between the pretransplantation MELD score and mortality in the first two years after liver transplantation

Abstract: The Model for End-Stage Liver Disease (MELD) score is now the criteria for allocation in liver transplantation for patients with chronic disease. Although the score has been effective in the prediction of mortality in patients awaiting liver transplantation, its abilities to predict posttransplantation outcome need study. The aim of this study is to compare outcome in the first 2 years after liver transplantation according to the pretransplantation MELD score. The study includes 669 consecutive patients who un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
128
3
5

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(146 citation statements)
references
References 12 publications
10
128
3
5
Order By: Relevance
“…Recently published data indicate that improved posttransplantation survival in HCV-infected patients is directly correlated with lower pretransplantation MELD scores. 24 In our study, the overall MELD score in patients who underwent LDLT, particularly in LDLT patients with HCC, was significantly lower than in CAD patients, and it could be postulated that outcomes in these patients would be improved when compared with CAD patients. When comparing LDLT patients without HCC (mean MELD score, 11) to patients with HCC (mean MELD score, 15.6) and CAD patients (mean MELD score, 28), there was no difference related to percentage of patients with HCV recurrence, time to recurrence, and graft and patient survival.…”
Section: Discussionmentioning
confidence: 48%
“…Recently published data indicate that improved posttransplantation survival in HCV-infected patients is directly correlated with lower pretransplantation MELD scores. 24 In our study, the overall MELD score in patients who underwent LDLT, particularly in LDLT patients with HCC, was significantly lower than in CAD patients, and it could be postulated that outcomes in these patients would be improved when compared with CAD patients. When comparing LDLT patients without HCC (mean MELD score, 11) to patients with HCC (mean MELD score, 15.6) and CAD patients (mean MELD score, 28), there was no difference related to percentage of patients with HCV recurrence, time to recurrence, and graft and patient survival.…”
Section: Discussionmentioning
confidence: 48%
“…10 However, a retrospective study of 669 patients found higher MELD score correlated well with decreased 1-and 2-year survival when patients were stratified into three groups (MELD score Ͻ15, 15 to 24, and Ͼ24). 11 Differences in survival between groups were statistically significant for patients with hepatitis C and noncholestatic liver disease only. There are no data correlating MELD scores with outcomes in the living donor liver transplant recipient population, and evolving data from cadaveric transplantation studies may not be applicable to LDLT.…”
Section: Discussionmentioning
confidence: 95%
“…Based on easily measurable laboratory data 2,5,6 , the MELD score has been considered more transparent and objective 2,5,7 for the ordination of liver disease on the waiting list for TH. Nevertheless, although it has been validated as a predictor of mortality in the list, the role of this scoring system for predicting survival after HT remains controversial 3,6,8 , which could suggest the need to readjust the graft allocation criteria for a model that also took into consideration the results of TH 8 . The objective of this study was to evaluate the accuracy of preoperative MELD score to predict survival after TH and also analyze factors predictive of mediumterm survival (24 months).…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%